2013
DOI: 10.1007/s00246-013-0828-8
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Abdominal Aorta Hemodynamics Are Associated With Necrotizing Enterocolitis in Infants With Hypoplastic Left Heart Syndrome

Abstract: Background The risk of necrotizing enterocolitis (NEC) in association with congenital heart disease is highest in patients with hypoplastic left heart syndrome (HLHS). Within the HLHS population, however, risk factors for NEC remain debated. We hypothesized that some infants with HLHS have vascular changes that contribute to gut hypoperfusion, independent of diastolic run-off and low cardiac output. Methods We analyzed the abdominal aorta pulsatility index and right ventricular function on routine pre-operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 21 publications
1
20
0
1
Order By: Relevance
“…This hypoperfusion could result in subtle hypoxic damage that increases the risk of developing NEC after birth. The potential association between bowel hypoperfusion and NEC has been described in neonates with hypoplastic left heart syndrome, coarctatio aortae and related abnormal abdominal aorta hemodynamics [12]. In this study, unbalanced interfetal transfusion was found significantly more often in MC multiples developing NEC, supporting our hypothesis.…”
Section: Discussionsupporting
confidence: 88%
“…This hypoperfusion could result in subtle hypoxic damage that increases the risk of developing NEC after birth. The potential association between bowel hypoperfusion and NEC has been described in neonates with hypoplastic left heart syndrome, coarctatio aortae and related abnormal abdominal aorta hemodynamics [12]. In this study, unbalanced interfetal transfusion was found significantly more often in MC multiples developing NEC, supporting our hypothesis.…”
Section: Discussionsupporting
confidence: 88%
“…(3, 5, 1012) Despite the high incidence of gastrointestinal morbidity and growth failure in the cardiac infant population, there is a paucity of knowledge regarding the specific intestinal mucosal and barrier insults incurred during neonatal cardiac surgery.…”
mentioning
confidence: 99%
“…Preoperative concerns reported in this survey included the risk of NEC, prostaglandin E1 (PGE1) use and presence of umbilical arterial catheter (UAC). NEC in congenital heart disease (CHD) is a universal concern which is associated with higher morbidity and mortality . McElhinney performed a case control study for development of NEC in 643 infants with CHD and showed that the diagnosis of HLHS was independently associated with development of NEC.…”
Section: Discussionmentioning
confidence: 99%